Wprowadzenie do dyskusji nad koncepcją opozycji politycznej - Pałecki, Krzysztof (Polityka i Społeczeństwo, 2020)
After the adoption of the understanding of political power as a game of social agency in a politically organized community, the author states that the scope of the subjectivity of both sides of power relations is variable, but the subjectivity of subordinates cannot be completely reduced. He defines political opposition as a normatively regulated and institutionally realized right to resist power entities.